Profile of David Kolb's Learning Style of Students on Biology Learning in the Distance Learning - Siti Azzkah Nurhasanah; Suharsono Suharsono; Dea Diella (Bioedukasi: Jurnal Pendidikan Biologi, 2021)
Distance learning in biology subject at Public Islamic High School (MAN) 1 Tasikmalaya City is considered less effective. Using the approaches based on students' learning styles can consider more effective. This research was conducted to determine the distribution of the learning styles of students of class XI MIPA about Biology with the methods of distance learning in MAN 1 Kota Tasikmalaya based on the theory of David Kolb. This research was conducted with a survey, and data analysis techniques using descriptive quantitative and qualitative following the Miles and Huberman. The sample used whole class XI MIPA (N=119 students). The instrument used is KLSI (Kolb Learning Style Inventory). The findings are students of MIPA in MAN 1 Kota Tasikmalaya has four learning styles, namely diverger, assimilator, converger, and accommodator. The most learning styles owned by the learners is the assimilator (31%), followed learning style accommodator 28%, learning style diverger 23% and learning styles converger 18%.